Peran Guru Terhadap Perkembangan Bahasa Anak Melalui Metode Bercerita Di KB Tunas Harapan - Yulia Marizal; Khairalfi Jumanisa Amril (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
Language development is one of the fundamental aspects of early childhood growth because it supports children's cognitive, social, and emotional development. However, many early childhood education institutions still encounter children who experience limitations in listening, speaking, expressing ideas, and communicating confidently. Therefore, teachers are required to implement appropriate learning strategies that can optimize children's language development. This study aimed to describe and analyze the role of teachers in improving children's language development through the storytelling method at KB Tunas Harapan Rimbo Kalam. This research employed a qualitative approach using a descriptive field research design. The participants consisted of two teachers and thirty-two children. Data were collected through classroom observations, in-depth interviews, documentation, and literature review. Data analysis was conducted using the interactive model of Miles and Huberman, including data reduction, data display, conclusion drawing, and data verification. Data validity was ensured through source and technique triangulation. The findings revealed that teachers played important roles as educators, facilitators, motivators, guides, evaluators, and language models during storytelling activities. The storytelling method significantly enhanced children's listening skills, enriched their vocabulary, increased their confidence in speaking, and improved their ability to retell stories using their own words. Interactive communication between teachers and children created meaningful learning experiences that supported optimal language development. It can be concluded that storytelling is an effective learning strategy for